PEMBERDAYAAN MASYARAKAT DESA PURWASARI, DRAMAGA, BOGOR, MELALUI KEGIATAN BUDIDAYA IKAN BAWAL (Colossoma Macropomum) DAN MAGGOT (Hermentia Illuciens L.) - Wildan Nurussalam; Apriana Vinasyiam; Daffa Nuradzani; Bulan Puspa Adamy; Naufal Taufiqurrahman; Fadly Adams Hamsyana; Husnadiva Naurah Kamal; Bintang Lazuardi; Intan Elisa Rahmawati; Shofii Amaliah Putri; Fierly January Ramadhina; Erwan Rusdiawan; Muhamad Saepul Akbar; Lutfi Nurhendra; Tiara Tiara; Ian Basmallah Nurdiansyah; Devita Adianti (Jurnal Abdi Insani, 2022)
Purwasari village has an unutilized resources for aquaculture activities, such as ponds, water from agriculture irrigation, and human resources in farmer groups. Despite the high interest in aquaculture activities that the people have, the aquaculture activities are still limited by the lack of knowledge regarding the technical aspect of aquaculture. Besides, the high price of the fish feed also becomes a primary limiting factor. This community service aimed to increase the community empowerment of Purwasari village by Tambaqui fish and maggot culture, to increase the profitability and food security of Purwasari village during the Covid-19 pandemic crisis. This activity was performed using a hybrid method, consisting of offline activities for the field survey, and controlling; online activities for distributing monthly questionnaires, and arranging a meeting between the university lecturer, speaker, and the villagers. This activity established a knowledge transfer from the university (Institut Pertanian Bogor) to the villagers. Based on the results of the questionnaire, this activity increased the knowledge, skill, number of members, and responsibility of the farmer group. Indicators of the physical improvement could be seen in the pond revitalization and infrastructure of the Tambaqui and maggot culture. This community service activity was applicable in Purwasari village and potentially increased the profitability and food security of Purwasari village during the Covid-19 pandemic crisis.